Deposition Environment Interpretation of Lemat Formation in the West Tanjung Jabung, Jambi Province - Daryono, Sapto Kis; Afrilita, Afrilita; Idarwati, Idarwati (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
The study of facies analysis and interpretation of the depositional environment of the Lemat Formation located on Bukit Tigapuluh aimed to clarify the problems found in Paleogene sediments in the South Sumatra Basin. The results of research on facies analysis and interpretation of the depositional environment of the Lemat Formation will provide an explanation and description of the history of the formation and stratigraphic evolution of Paleogene-aged sedimentary rocks in the South Sumatra Basin as reflected in their lithological and facies characteristics. A detailed analysis of fluvial facies was carried out in the West Tanjung Jabung area, Jambi Province. A stratigraphic cross-section was prepared with an accumulated thickness of ± 25 m. The stratigraphic section included two rock deposits, namely sandstone-quartz deposits and conglomerate deposits. Analysis of lithofacies and architectural elements of the study area indicated a fluvial depositional environment. The resulting architectural elements consisted of six associations: channel (CH), scour hollows (HO), gravel bedform (GB), sediment gravity flows (SG), sandy bedform (SB), and floodplain fines (FF). The dominance of sedimentary material, which tends to be coarse, and the many facies associations GB, SG, and SB indicated many river bars and were characteristic of braided rivers. The obtained interpretation of the depositional environment was Conglomerate deposits in the Alluvial Fans System with Gravity Flow River environment or gravel bed braided river, and sandstone-gravel deposits in the shallow environment or gravel bed braided river.